Time Course of Changes in the Concentration of Peroxides and Superoxide Dismutase in Females with Gestosis in the Perioperative Period - V. M. Zhenilo; I. V. Mikhno (Общая реаниматология, 2007)
Objective: to study the level of peroxides and the activity of superoxide dismutase (SOD) in females with gestosis in the perioperative period.Materials and methods: 85 females in whom delivery had been performed under spinal anesthesia using conventional perioperative intensive care were examined. A control group comprised 30 females with uncomplicated pregnancy; Group 1 included 26 females with moderate gestosis; Group 2 consisted of 29 females with severe gestosis. The severity of gestosis was determined by means of the Goecke scale that had been modified by G. M. Savelyeva. The groups of the examinees were matched by height, weight, age, and gender.Results: there is intensification of free radical processes and a standard adaptive response of the antioxidative system forms in the pregnant females exposed to surgical delivery under spinal anesthesia. In dynamics, this reaction is characterized by a certain pattern: the maximum activation on the first postoperative day, some depletion on day 3, and recovery of compensatory capacities on day 5. The antioxidative system of the females with uncomplicated pregnancy generally shows a balanced response to activated free radical processes during surgical delivery and in the postoperative period. There is stress in moderate gestosis-complicated pregnancy and depletion of the antiox-idative system in severely progressive gestosis, which diminishes the body’s adaptive capacities and leads to the formation of chronic oxidative stress as a leading factor of the pathogenesis of the disease. Imbalance between free radical oxidation processes and the antioxidative system increases when surgical delivery is performed. In the females with moderate gestosis, oxidative stress may be characterized as subcompensated with a moderate increase in the concentration of peroxides in the intra- and postoperative period, as compared with those with physiological pregnancy.Conclusion. Severe gestosis is characterized by a decompensated stress with a pronounced increase in the level of peroxides before and during surgical delivery and within 5 postoperative days.